Pengaruh Sikap Dan Persepsi Terhadap Niat Komplain Pelanggan Pada Stasiun Yogyakarta Daerah Operasi Vi Yogyakarta - ependi, ahmad; Riyanta, Wawan (Politeknik Perkeretaapian Indonesia Madiun, 2020)
Kereta Api Indonesia needs to know the attitude and perception of passengers in complaining the train services in order to not causing losses. Attitude and perception described in several aspects that affect the intention of customer complaints, so that the influence between these aspects will be known. This study used a causal research design which needs to see one or more variables that cause or be a determinant of other variables. Data use Smart PLS with the help of Smart PLS 2.0 M3 software. The results of the study shown that the attitude towards complaints behavior affects the intention of complaint to operator, the attitude towards complaints behavior is influenced by Consumer Avoidance, Complaint Experience, and ability to control. The perception of complaint's value affects the intention to complain, the perception of the value of complaints is influenced by Consumer Avoidance, Complaint Experience and ability to control. Perception of possible complaint which succeeded in influencing the intention to complain, and are influenced by the ability to control, while the factor of Customer Avoidance and Complaints Experience do not affect the perception about the possibility of successful intentions. complaints to the operators.